Strategy of Agricultural Extension Agents Implementation to Increase Rice Productivity - Prakoso, Hafiidh; Prajanti, Sucihatiningsih Dian Wisika (Efficient: Indonesian Journal of Development Economics, 2021)
The purpose of this study was to analyze the conditions of agricultural extension activities in Pati Regency, analyze problem agricultural extension agents face in increasing their role, and analyze the implementation strategies of agricultural extension agents to increase the level of wetland paddy productivity. The research method used is qualitative descriptive method with SWOT analysis. The subjects of this study were 43 agricultural extension officers and 3 key persons. The results showed that the condition of the extension activities in Pati District was running quite well. The obstacles faced by extension workers include: Policies that often clash with extension activities and the farmers themselves; Efforts to increase human resources of agricultural extension agents through training are still lacking; and The proportion of field agricultural extension agents to the assisted farmer groups is still too unequal. The following strategies for implementing agricultural instructors to increase lowland rice productivity in Pati Regency are: Online consultation services; Testimonials of successful implementation of extension; Breakthrough alternative fertilizers and treatments; Incentives based on length of work; and Management of counseling and evaluation time. Tujuan penelitian ini adalah untuk menganalisis kondisi kegiatan penyuluhan pertanian di Kabupaten Pati selama ini dan apa saja yang dihadapi oleh penyuluh pertanian dalam meningkatkan perannya. Metode penelitian yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif dengan analisis SWOT. Narasumber dari penelitian ini adalah 43 penyuluh pertanian di enam BPP kecamatan yang ada di Kabupaten Pati dan 3 penyuluh dinas. Hasil penelitian menunjukkan bahwa kondisi kegiatan penyuluhan di Kabupaten Pati sudah berjalan cukup baik. Kendala yang dihadapi penyuluh diantaranya kebijakan yang seringkali berbenturan dengan kegiatan penyuluhan maupun petani itu sendiri, upaya peningkatan SDM penyuluh pertanian melalui pelatihan masih dirasa kurang, dan umur dari penyuluh rata-rata 45 sedangkan upaya regenerasi masih dirasa sulit. Dengan analisis SWOT, strategi implementasi penyuluh pertanian untuk meningkatkan produktivitas padi sawah di Kabupaten Pati adalah layanan konsultasi daring, testimoni keberhasilan penerapan penyuluhan, terobosan alternatif pupuk dan perawatan, insentif berdasarkan lama kerja, manajemen waktu penyuluhan dan evaluasi.